Bioactive Compounds and Biological Assays of different Prosopis Juliflora Extracts against Groundnut Aphid - Mulate Zerihun; Estifanos Ele (Open Journal of Chemistry - Peertechz Publications, 2020)
Natural products from medicinal plants, either as pure compounds or as standardized extracts, provide unlimited opportunities for different purposes. Botanical preparations of medicinal plants for insecticidal usage contain various types of bioactive compounds. The aim of this paper focuses on the botanical evaluation of stem bark, seed and leaf extracts of Prosopis juliflora for their insecticidal effect against groundnut (Aphis craccivora) aphids. Extracts with the concentrations of 1, 2.5, 5, 10 and 15% weight by weight percentage were tested. The highest mortality rate of the groundnut aphid that was recorded after 12 h, due to the methanolic and dichloromethane extracts, was 83.33%. The advantages and problems of different extraction techniques were tested and discussed. Different chromatographic techniques were employed to identify, isolate and characterize secondary metabolites. Two compounds, 4-(2-aminoethyl) phenol (1) and 3-O-methyl-chiro-inositol (2) were isolated from the methanolic extract of the leaves part. Structural elucidations of the isolated compounds were based on their 1H NMR, 13C NMR, UV and IR spectra.